Socialisation and character education in the Muslim world: exploring the role, impact, and necessity of indoctrination - Allison, Safwaan Zamakda (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2024)
This investigation seeks to understand the importance of imparting character education to students across the educational spectrum. It examines the intricate nexus lying between shared boundaries that form the provision of education, socialisation, and indoctrination. It delves into the multifaceted elements of character education, emphasising the transmission of moral, social, religious, and ethical values. By analysing the role of educators as key influencers, the research underscores the challenges in fostering positive characteristics amidst the modern digital landscape and diverse cultural contexts, particularly in the Muslim world. The study employs a qualitative descriptive approach, utilising a narrative literature review to understand the subjective aspects of morality and social values and appreciate the importance of character education within religious and secular frameworks. There is no doubt that education has a profound impact on students, especially in their formative years, shaping them into moral, well-behaved, and intelligent members of society. It should equip students with the knowledge and character to thrive as contributing citizens, both locally and globally, in the digital age. This study found that teachers are somewhat reluctant to be accused of ‘indoctrination’, but this is inherently an integral element of education, and should therefore be embraced, acknowledged, and used for good: instilling critical thinking, along with a moral compass and the values needed to be upstanding and successful members of society.